DIETHANOLAMINE AS CO2 ABSORBENT FOR 14C ANALYSIS TO DETERMINATION AGE OF CORAL REEF FROM PANAMBUNGAN ISLAND BY USING LIQUID SCINTILLATION COUNTING (LSC) METHOD - Seniati Salahuddin; Alfian Noor; Muhammad Zakir (Hasanuddin University, 2017)
Utilization of diethanolamine (DEA) as an absorbent for 14C analysis using liquid scintillation counting (LSC) on the determination of the age of the coral reefs have been done. Coral reefs are analyzed from the uninhabited Panambungan island which far away from the influence of human activity. Sample preparation, physical and chemical by using 2 acid-base mixture: H2O2-NaOH and HClO4-HCl. At this stage there is a weight reduction of as much as 9.023 gram sample. Carbonate samples reacted with HCl to separate CO2 and sequestration by diethanolamine into carbamate compounds. Total carbon in the sample solution is obtained through the reduction of 0.838 grams before and after absorption. The specific activity of 14C in samples measured by the counter LSC HIDEX 300 SL and obtained 8.4026 ± 6,85 DPM/gC. The specific activity of the sample and the specific activity of modern carbon (15.3 ± 0.1 DPM/gC) is inserted into the equation radioisotope decay, obtained the age of 4955 ± 935 years.